CELEBRITY ENDORSEMENT, PERCEIVED AI INTELLIGENCE, AND DIGITAL FIRM INTIMACY: A MIXED-METHODS STUDY ON SOCIAL MEDIA PURCHASE DECISIONS - Hasibuan, Reza Rahmadi; Suliyanto; Novandari, Weni (Veredas do Direito, 2025)
Purpose – This study aims to analyze the direct and indirect effects of celebrity endorsement on consumer purchasing decisions in the context of live streaming on social media, with the mediating role of digital firm intimacy and perceived AI intelligence. Design/methodology/approach – This study uses a mixed-method approach. The quantitative study involved 412 active users of TikTok and Instagram Live who had interacted with celebrity content and AI-based features. Analysis was conducted using PLS-SEM to test the relationships between constructs and mediation effects. Meanwhile, qualitative research was conducted through semi-structured interviews with 10 informants, consisting of representatives from technology institutions and millennial and Gen Z consumers, analyzed using thematic content analysis. Findings – The results indicate that celebrity endorsement has a significant direct effect on purchasing decisions, as well as on both mediating constructs. However, only digital firm intimacy was found to significantly mediate these relationships. Qualitative findings support that emotional engagement during live streaming is more decisive for purchasing decisions than perceptions of technological sophistication. Originality/value – This study contributes theoretically by integrating emotional and technological approaches into a single digital marketing framework. The concept of digital firm intimacy is introduced as a bridge between celebrities, technology, and purchasing decisions. Additionally, this study provides empirical insights into the limitations of consumer perceptions of AI and emphasizes the importance of building authentic interactive experiences in digital marketing strategies.